Effect of Temperature Variations of Corn (Maize) Oil Biodiesel on Torque Values and Thermal Efficiency of Diesel Engines - Suardi, Suardi; Ikhwani, Rodlian Jamal; Aulia, Ade Putri Rezki (Universitas Negeri Malang, 2023)
The trend of consumption of hydrocarbon fuels in Indonesia, which is increasing every year, is not accompanied by the amount of production, which is decreasing. Alternative fuels to reduce dependence on hydrocarbon fuels. One form of alternative fuel is biodiesel, which is made from corn (maize) oil. Corn oil itself, if processed, can be an option for clean and environmentally friendly energy option and that is the main objective of this research is to determine the performance of biodiesel corn oil on diesel engines. The method used in this study is an experimental method where corn oil biodiesel is tested directly on a testing machine. The data from the test results will be used to find the torque and thermal efficiency values so that the engine performance values for each fuel variation can be identified. The results of the study obtained the engine performance value, namely the highest torque was on diesel oil fuel 4.57 N.m. The highest thermal efficiency value achieved at the B30 fuel sample at a temperature of 60 °C with the thermal efficiency of 17.4 percent. With these results, it can be concluded that engine performance with corn oil fuel can be used as an alternative fuel to replace hydrocarbon fuel.